10s-5+3=9s+2

Simple and best practice solution for 10s-5+3=9s+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10s-5+3=9s+2 equation:


Simplifying
10s + -5 + 3 = 9s + 2

Reorder the terms:
-5 + 3 + 10s = 9s + 2

Combine like terms: -5 + 3 = -2
-2 + 10s = 9s + 2

Reorder the terms:
-2 + 10s = 2 + 9s

Solving
-2 + 10s = 2 + 9s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-9s' to each side of the equation.
-2 + 10s + -9s = 2 + 9s + -9s

Combine like terms: 10s + -9s = 1s
-2 + 1s = 2 + 9s + -9s

Combine like terms: 9s + -9s = 0
-2 + 1s = 2 + 0
-2 + 1s = 2

Add '2' to each side of the equation.
-2 + 2 + 1s = 2 + 2

Combine like terms: -2 + 2 = 0
0 + 1s = 2 + 2
1s = 2 + 2

Combine like terms: 2 + 2 = 4
1s = 4

Divide each side by '1'.
s = 4

Simplifying
s = 4

See similar equations:

| 3+2x-1x-1=3x-6 | | 50h+75=65 | | 2.5x=.5x+150 | | -x/8+3=9 | | -13=r-17 | | 37-c=23 | | 12x^4-13x^2+5=0 | | ax^2+2x+4=0 | | 18+-128= | | 3/4-r=-1/3 | | 13x^4+9x^2+2=0 | | 8nr^6h+8nr^9= | | 12b^3-8b=0 | | 10s-5+3=3(3s+2) | | y=0.2x^2-7 | | A=k+ab+5b-3b | | 6(.75)-10=2(.75)-7 | | 64+-1= | | 15ab-35ab^2= | | k=ab+5b-3b | | 5/2c=8/1/3 | | -40=6-6s | | 4x*2x=y | | 7-2j+8J-3= | | k=ab+5b-3b(fora) | | -5+18-24= | | -5[w-3]=45 | | x+1=55 | | 4b-15=13 | | (4x^2)-68x=-120 | | k=ab-5b+3bfora | | 4(4x+8)=128 |

Equations solver categories